CURRETNLY CONDUCTED EDUCATIONAL REFORMS IN UKRAINE: ACHIEVEMENTS AND NEW CHALLENGES - Бобрицька, В. І. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2019)
The article proves the fact that current reforms take place in the system of education of Ukraine taking into account the latest social challenges and priority tasks of the legislative and executive branches of power, in particular, those which aimed to improve the efficiency of education, to overcome territorial differences in the quality of providing it, to modernize the content of education in accordance with relevant labour market demands, to support the process of implementing academic integrity in both educational and academic institutions. The goal of the study has been met, namely there has been conducted the analysis of the effectiveness of educational reforms in Ukraine by processing the data obtained from interviews with different stakeholders of the educational process, who were the students (future teachers), practicing teachers, and lecturers of higher education institutions. There were applied the further outlined research methods like: first, logical and system analysis was intended to summarize the views of the participants of the focus groups on the requests and expectations of the state, civil society and educators to reforms in the field of education; second, documents examination was supposed to identify the participants’ standpoints on the amendments made to the Law of Ukraine «On Education» (2017) and the Conceptual Principles of Secondary Education Reform «New Ukrainian School» (2016). The article reveals the requests and expectations of the state, civil society and educators from conducting the reforms in the field of education. Based on the opinions of the focus group participants on the strategic aspects of the Law of Ukraine «On Education» and the Conceptual Principles for the Reform of the Secondary School «New Ukrainian School», we performed the ranking of the respondents’ standpoints on the relevance of amendments, and we discovered those concepts needed further clarification (decentralization and effective management that will provide real autonomy to the school, a new school structure that allows mastering the new content and gaining competencies for life, the timeline for implementation of the reform). We revealed the prevailing attitudes of educators, their needs and expectations concerning outputs of educational reforms in Ukraine, namely: respect for their job from the society, trust for the teacher; decent fees, proper and transparent financing of educational institutions; real academic freedom, etc.